PERAN BADAN PENASIHATAN PEMBINAAN DAN PELESTARIAN PERKAWINAN DALAM MENGANTISIPASI ANGKA PERCERAIAN (Studi Pada BP4 Kabupaten Labuhanbatu Raya) - Pagar, Sudirman Suparmin, Ali Bata Ritonga (AT-TAFAHUM: Journal of Islamic Law, 2018)
The big point of this research is how does the role ofÂ  advising council and preservation of marriage as the council of advising and preservation of marriage at regency of Labuhanbatu Raya contribute. The purpose of this research to analyze about the role of advising council and preservation of marriage as the council of advising and preservation of marriage at regency of Labuhanbatu Raya which didÂ  provide the government.The result of this research (qualitative method) is to decide that program plan of BP4 on the affordable to oppress the enlarging of divorce rates at regency of Labuhanbatu Raya is programmed and rolled section law BP4 decision, and the formulation of BP4, based on Islamic law as the running all at Pancasila as the ideology based on socialization about honesty marriage, mawaddah, wa rahma and takwa. And the affordable of BP4 to oppress the divorce rates at regency of Labuhanbatu Raya is going spirit to do national movement, this program is running well as the founding honesty marriage for every months based on frame work and reformation agenda on social custom and affordable to create the highest communitiesâ moral, faithful, worship and honorable attitude. Meanwhile the obstruction factor divided to internal and external. And the support factor is the communities hope and support toward being on have honesty marriage.